Research Dynamics in Social Entrepreneurial Orientation: A Bibliometric Analysis Based on Citations and Publications - Kurniawan, Kurniawan; Iskandar, Yusuf (Poltanesa, 2024)
This paper explores the dynamic field of Social Entrepreneurial Orientation (SEO), which melds entrepreneurial tactics with social goals, aiming to address pressing societal issues such as poverty and environmental sustainability. This study examines SEO's academic discourse and impact through a systematic bibliometric analysis spanning thirteen years (2011-2024), employing data from key databases like Scopus and Web of Science. The research illustrates significant growth in SEO scholarship, evidenced by increasing publications and citations, highlighting the field's expanding influence across academic and practical domains. Our analysis utilizes VOS Viewer for trend analysis, author influence mapping, and thematic clusterization, revealing a rich tapestry of collaborative research and evolving themes such as innovation and sustainability. The findings suggest that while the field has robust scholarly engagement, there is room for methodological advancement to enhance the long-term understanding of SEO's impacts. This study underscores the importance of SEO in fostering sustainable business practices and proposes strategic frameworks that can guide future research, policy-making, and business strategies, aiming to integrate entrepreneurial vigor with societal well-being. Through this scholarly inquiry, the paper contributes to a deeper understanding of SEO's role in driving social change and emphasizes the need for global and interdisciplinary collaborations to tackle broad societal challenges effectively.